Influence of bacterial inoculation on growth and plant nutrition of peach grafted in different rootstocks in calcareous soil - İpek, Muzaffer; Arıkan, Şeyma; Eşitken, Ahmet; Pırlak, Lütfi; Dönmez, Mesude Figen; Turan, Metin (Penerbit Universiti Kebangsaan Malaysia, 2021)
The highly calcareous soil limits plant growth parameters due to inadequate uptake of plant nutrients. Calcareous soil conditions affect plant growth through impaired chlorophyll synthesis, root growth, enzyme synthesis, and nutrient uptake. To overcome the negative effect of calcareous soil, six bacterial strains namely Alcaligenes 637Ca, Agrobacterium A18, Staphylococcus MFDCa1, Staphylococcus MFDCa2, Bacillus M3, and Pantoea FF1 were inoculated in one-year-old plants of peach cultivar ‘Elegant Lady’ grafted onto GF677 and Nemaguard rootstocks. The bacterial treatments were observed to improve plant growth and nutrient content compared to the control. Moreover, the GF677 rootstock was observed to be more tolerant to high calcareous soil conditions than Nemaguard, showing better plant growth and nutrient content. At the Nemaguard rootstocks, the largest leaf area was observed to be upon inoculation with MFDCa2 (29.1 cm2), FF1 (28.8 cm2), and M3 (28.1 cm2), whereas at the GF677 rootstock, the highest leaf area was observed upon inoculation with MFDCa1 (34.7 cm2), FF1 (32.6 cm2), and 637Ca (31.5 cm2). The leaf iron content was higher in bacterial treatments than the control. In the Nemaguard rootstock, the highest iron content was measured in plants inoculated with 637Ca (133.49 mg kg–1) and M3 (127.64 mg kg–1), whereas in the GF677 rootstock, the treatments MFDCa1 (131.51 mg kg–1), 637Ca (131.21 mg kg–1), FF1 (127.72 mg kg–1), and M3 (127.68 mg kg–1) resulted in high iron content. The results indicate that bacterial inoculations have a significant potential to improve plant growth and can be used as biofertilizers for peach grafted onto Nemaguard and GF677 in high calcareous soil conditions.